TEP or TAPP: who, when, and how? - Iossa, Angelo; Traumueller Tamagnini, Giovanni; De Angelis, Francesco; Micalizzi, Alessandra; Lelli, Giulio; Cavallaro, Giuseppe (Frontiers in Surgery, 2024)
Groin hernia repair is the most common procedure performed by general surgeons. The open mesh technique generally represents the main technique for an inguinal repair, but a different approach is often required. Laparoscopy was found to be the answer to minimizing the impact of the preperitoneal open techniques described by Nyhus and Stoppa. The introduction of the totally extraperitoneal hernia repair (TEP) and transabdominal preperitoneal repair (TAPP) in the early 1990s started a new chapter in groin hernia surgery. The minimally invasive techniques vs. open mesh, and then one against the other, soon became a hot topic among abdominal wall surgeons. With time, the number of procedures and indications increased and are still increasing. This review aims to provide an overview of the two main laparoscopic techniques for groin hernia repair, answering the following questions: Who should perform them? What is the learning curve required to minimize complications and optimize operative time? When is a minimally invasive approach indicated, and which one (both in elective and in emergency setting)? How are they performed? The standard techniques have been described in detail, and personal observations from an abdominal wall surgery referral center were added. The main reviews from the early 2000s up to date, which compared the techniques, were analyzed, and the results reported, confirming the comparable safety and efficacy of both these techniques.